Leadership presence: how do you show up? - Virgilio, Laura (Henry Stewart Talks, 2020)
Definition of emotional intelligence and its role in the workplace, Measuring emotional intelligence, Scoring and Self Reporting, The EQi 2.0 model and its composites, The model applied to leadership